Assessment of Fruit and Vegetable Losses at Major Wholesale Markets in Nepal - Devkota, A. R.; Dhakal, D. D.; Gautam, D. M.; Dutta, J. P. (International Journal of Applied Sciences and Biotechnology, 2014)
A study regarding the losses of harvested horticultural produces in the major fruit and vegetable wholesale markets of Nepal was conducted to identify the major causes of fruits and vegetable wastage. This study aimed at generating useful information about the causes of loss of horticultural produce, types of loss and also about the possibility of reuse and recycling of such organic wastes as resource for composting and vermicomposting. Survey of the three major market centers namely; Narayangadh, Pokhara, and Kalimati fruit and vegetable wholesale market was conducted. Forty five wholesalers and 90 retailers were selected for the study. Data were collected using structured questionnaires. From regression analysis it was concluded that lack of cold storage facility and inappropriate packaging facility had significant effect on the loss of the produce. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11551  Int J Appl Sci Biotechnol, Vol. 2(4): 559-562